Milk Composition and Quality of Sahiwal Friesian Crossbred Cow Studied in Malaysia (The Agriculturists, 2013)
Six groups of Sahiwal-Friesian crossbred cows, namely M50-1, M50-2, M50-3, M56, M63 and M75-1 were evaluated. In total 180 cows were used and milk collected was evaluated for composition and quality. The effect of genotypes was significant (P?0.05) only for titrable acidity (TA) and milk yield (MY). The M50-1 had the highest milk yield per day (8.73 ± 1.65 kg) but this was not significantly different from the yields of M50-3, M56 and M75-1 (7.06 ± 0.84, 7.06 ± 0.96, 7.70 ± 0.82 kg), respectively. Lactation stage had significant (P?0.05) effect on milk yield, fat content, solids-not fat (SNF) content, total solid (TS) content, moisture content and specific gravity (Sp. Gr). Fat content at early lactation was significantly (P?0.01) lower than at middle and late lactation (3.69 vs 4.27 and 4.50, respectively). SNF content for middle lactation was significantly lower (P?0.05) than that at early and late lactations. At late lactation, TS and moisture contents were significantly (P?0.05) higher than those at early lactation. The range of milk composition and quality such as fat (3.96 - 4.50%), SNF (9.02 - 9.40%), TS (13.01-13.81%), moisture (86.26 - 87.07%), Sp.Gr. (1.030- 1.031), pH (6.74 - 6.91), TA (0.13 - 0.15%), MBRT (6.50 -7.40 h) belonged to normal range. M50-1, M50-3, M56 and M75-1 had higher test day milk yield. The optimum level of Friesian inheritance in combination with Sahiwal for MY appeared to be 75%, 56% and 50% with selection for milk production. The composition and quality of milk from the Sahiwal - Friesian crossbred cows met the required standard. DOI: http://dx.doi.org/10.3329/agric.v11i2.17488 The Agriculturists 2013; 11(2) 58-65